Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas XI IPA 4 Semester II SMA Negeri I Bengkalis Tahun Pelajaran 2010/2011 - Rodiah Rodiah (STAIN Bengkalis, 2017)
Teachers have tried to use a media to improve learning activities.The focus of this research is to inprove student learning outcomes through cooverative learning type STAD.The purpose pf this research is to inprove learning achievement and motivation in the group of studys.The research was conducted at the second semester of the XI grade majoring in natural science registered in 2010/1011 academic year in a public senior haigh school in Bengkalis.This classroom research was carried out in two circiles.Each circle followed four steps:planning ,action,observation and reklection.The data were collected though the use of a : i) observation sheet for learning activities, and ii)there was also an increase in students learning achievement.Therefore,the finding of the research concluded that the use of learning in cooverative learning type STAD of hemimal increased students achievement.